COMPARATIVE ANALYSIS OF POTENTIAL BANKRUPTCY OF CONVENTIONAL TAXI COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE - Kadek Indah Putriningrum; Sayu Ketut Sutrisna Dewi (Adisam Publisher, 2024)
Bankruptcy is a condition where a company is no longer able to pay off its obligations. For this reason, companies need an early warning that can be used to detect bankruptcy that could be detrimental to the company. There are early indications of a company that can be recognized early if the financial statements are analyzed carefully in a certain way. This research aims to determine the prediction of potential bankruptcy of conventional taxi companies listed on the Indonesia Stock Exchange (BEI) using Altman (Z-Score), Springate (S-Score), and Grover (G-Score) analysis. The type of research used in this research is descriptive research with a quantitative approach. The data used in this research are the financial reports of the companies PT Blue Bird Tbk and PT Express Transindo Utama Tbk for the 2019-2022 period which were published on the Indonesia Stock Exchange website. The research results show that the Altman (Z-Score), Springate (S-Score), Grover (G-Score) methods show different value results. The differences in predicting potential bankruptcy in the three methods are found in the ratios used as well as differences in cut off values for each bankruptcy method. Based on the results of calculations using these three methods, it can be seen that the company PT Express Transindo Utama Tbk has more potential to experience bankruptcy compared to the company PT Blue Bird Tbk in the 2019-2022 period.